Androgen tic alopecia (AGA) -New Approach (Bangladesh Journal of Dental Research & Education, 2015)
Androgen tic alopecia is a no scarring progressive miniaturization of the hair follicle with a usual characteristic pattern distribution in genetically predisposed men 1. It is the most common hair loss disorder which causes significant impairment of life 2,3. The frequency and severity of male AGA increases with age in all ethnic groups 4.Bangladesh Journal of Dental Research and Education Vol.5(2) 2015: 64-65